(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The ability of I and III instar larvae of Plodia interpunctella to find food was evaluated in a polypropylene one way olfactometer. As attractants an artificial diet, corn meal, almonds and raisins were used. The attraction of artificial flavours used in the bakery industry was tested on III instar larvae: almond, hazelnut, Sicily lemon, chocolate and croissant. The higher number of I instar larvae was observed on artificial diet and corn meal as far as 3 m distance. III instar larvae are indifferently attracted by the substrates as far as 4 m; the artificial diet and corn meal resulted the most attractive ones as far as 5 and 6 m distance. Only few larvae were attracted by flavours.